Analysis sensory edible film from Banggai yam starch phosphate - Chaniago, Ramadhani; Hasanuddin, Asrani; Rahim, Abdul; Lamusu, Darni (Environmental and Agriculture Management, 2024)
Resilience and acceptance sensory edible film from phosphorylated sweet potato starch​ with concentration different glycerols​ Still Not yet fully answered, necessary There is effort for varying the concentration glycerol influence characteristic mechanical and functional from edible film. research This proposed for to study variation concentration glycerol influence characteristic Mechanic from edible film so that to obtain evaluation from panelist related sensory. Analysis sensors used​ for to obtain character product in accordance with what is received by the senses sight, smell, taste, and touch. Analysis sensory in study This involving student from Faculty Agriculture Department of Tadulako University as many as 15 people (Hamsiohan, 2019) . Edible film samples cut small and tested color, texture, aroma, and power accept in a way overall use scale hedonic 7 points namely 7 = really lik, 6 = really like, 5 = like, 4 = neutral, 3 = no like, 2 = very much not like, 1 = very much not like. Panelist evaluate attributes provided​ in scale hedonistic in accordance with preference them. Based on results and discussion, then study This conclude that analysis sensory that is color (2.5 – 5.3) or (no like / dislike very much like - like); texture 2.3 – 5.6 or (very dislike) like – really like); aroma (3.1 – 6.6) or no like – really like) ; overall (2.6 – 5.2) or (no up to).